China's Rise to Power
IX, 248 p.
Keywords: China's combination of authoritarian rule and a market-oriented economy has proven simultaneously appealing and a source of domestic discontent. This essay collection balances policy analysis with detailed investigation of escalating popular unrest to anticipate the future of Chinese governance & society.